Effects of magnetic fields of up to 9.4 T on resolution and contrast of PET images as measured with an MR-BrainPET. - N Jon Shah (Public Library of Science (PLoS), 2014)
Simultaneous, hybrid MR-PET is expected to improve PET image resolution in the plane perpendicular to the static magnetic field of the scanner. Previous papers have reported this either by simulation or experiment with simple sources and detector arrangements. Here, we extend those studies using a realistic brain phantom in a recently installed MR-PET system comprising a 9.4 T MRI-scanner and an APD-based BrainPET insert in the magnet bore. Point and line sources and a 3D brain phantom were filled with 18F (low-energy positron emitter), 68Ga (medium energy positron emitter) or 120I, a non-standard positron emitter (high positron energies of up to 4.6 MeV). Using the BrainPET insert, emission scans of the phantoms were recorded at different positions inside and outside the magnet bore such that the magnetic field was 0 T, 3 T, 7 T or 9.4 T. Brain phantom images, with the 'grey matter' compartment filled with 18F, showed no obvious resolution improvement with increasing field. This is confirmed by practically unchanged transaxial FWHM and 'grey/white matter' ratio values between at 0T and 9.4T. Field-dependent improvements in the resolution and contrast of transaxial PET images were clearly evident when the brain phantom was filled with 68Ga or 120I. The grey/white matter ratio increased by 7.3% and 16.3%, respectively. The greater reduction of the FWTM compared to FWHM in 68Ga or 120I line-spread images was in agreement with the improved contrast of 68Ga or 120I images. Notwithstanding elongations seen in the z-direction of 68Ga or 120I point source images acquired in foam, brain phantom images show no comparable extension. Our experimental study confirms that integrated MR-PET delivers improved PET image resolution and contrast for medium- and high-energy positron emitters even though the positron range is reduced only in directions perpendicular to the magnetic field.